ANALYSIS OF THE LEVEL OF PUBLIC UNDERSTANDING OF ISLAMIC BANKING (CASE STUDY OF THE PEOPLE OF PEKAN KUALA VILLAGE, KUALA DISTRICT, LANGKAT REGENCY - Ulen Bangun; Listiadiyanti Br Sitepu (Proceeding International Seminar of Islamic Studies, 2021)
This study aims to determine the analysis of the level of public understanding of Islamic banking (Case Study of the People of Pekan Kuala Village, Kuala District, Langkat Regency).This study uses a descriptive method using qualitative data.The results of this study indicate that the understanding of the community about Islamic banksin theKelurahan Pekan Kuala, Kuala Subdistrict, Langkat Regency isthat thecommunity only knows about the existence of Islamic banks but does not understand Islamic banks in detail.Only some peoplewhounderstand aboutIslamicbanksand some even don't know about Islamic banks at all.Most people don't know about products andserviceswhatever is in the Islamic bank.Lack of understanding from people as minimnya dar information obtaineditheIslamic banks as well as media such as television,mediaprint andmediasocial causes people not knowing what it was Islamic banks as well as any productjustin Islamic banks.The factorsthatcause the level of understanding of the people of Pekan Kuala Kelurahan, Kuala Subdistrict, Langkat Regency, about Islamic banking are smaller than conventional banking, namely: Knowledge, Past Experiences, Social or Environmental Factors, andInformationFactors. Keywords: Community Understanding Level, Islamic Banking